Step-by-step explanation:
Find the slope.
[tex]m = \frac{ - 1 - 3}{0 - 2} = \frac{ \: \: \: 4 \: }{ - 2 \: } = - 2[/tex]
Point-slope form.
[tex]y - y1 = m(x - x1)[/tex]
Using the given and gathered information.
[tex]y - 3 = - 2(x - 2)[/tex]
^Point-slope form^
If you want y-intercept form:
[tex]y = mx + b[/tex]
Since we previously found the Slope, we now need to find the y-intercept.
[tex]y = mx + b \\ 3 = - 2(2) - b \\ 3 = - 4 - b \\ + 4 = + 4 \: \: \: \: \: \: \: \: \: \: \\ 7 = b[/tex]
Using the information given and gathered.....
[tex]y = - 2x + 7[/tex]
^y-intercept form^